SOURCES OF IGNEOUS ROCKS AND GENESIS OF THE EARLY MESOZOIC TECTONOMAGMATIC AREA OF THE MONGOLIA-TRANSBAIKALIA MAGMATIC REGION: 2. PETROLOGY AND GEOCHEMISTRY - Kovalenko V.I.; Yarmolyuk V.V.; Budnikov S.V.; Sal'nikova E.B.; Kovach V.P.; Kotov A.B.; Ponomarchuk V.A.; Kozlov V.D.; Vladykin N.V.; Khanchuk A.I. (My University, 2003)
According to the results of isotopic and geochemical investigations (neodymium, strontium, and oxygen isotopes and trace elements), the Early Mesozoic rocks of the Mongolia-Transbaikalia magmatic area were derived from mantle and crustal sources. The batholith core of the area and the leucogranites, granosyentites, lithium-fluorine granites, and some peralkaline granites of marginal zones were formed under the major role of crustal anatexis. The melts were generated in a mixed source composed of ophiolites and sediments. The neodymium and oxygen isotopic characteristics of the batholith granitoids suggest an increase in the fraction of juvenile components (igneous rocks of Caledonian ophiolites) at the expense of sedimentary (pelitic) rocks and a decrease in the degree of source melting with increasing silica content. A degree of melting close to one produced the most basic granodiorites of the batholith; the leucogranites were derived at a degree of melting of about 0.75; and the lithium-fluorine granites, at about 0.5. The predominant component of the source of batholith granitoids is sedimentary rocks (pelites) with a considerable admixture of the material of the pre-Caledonian continental crust characterizing the sedimentary filling of the Khentei trough. Mantle magma sources (DM or HIMU + EMU + occasional admixture of continental crust) were established for bimodal basalt-comendite associations and a number of peralkaline granites. Zhanchivlan plagiogranites were formed in a subduction environment through melting of the oceanic crust presumably of the Indosinides of the Mongolia-Okhotsk basin. A model was proposed for the formation of the zonal magmatic area of the Mongolia-Trans-baikalia region accounting for the participation of sublithospheric (mantle plume), lithospheric (subduction), and crustal sources.
Keywords: Mesozoic; Mesozoic; Мезозой